Improving kidney transplant care through the application of continuous glucose monitoring - a narrative review - Tan, Jackson; Khalil, Muhammad Abdul Mabood; Avari, Parizad; Leelarathna, Lalantha (Frontiers in Nephrology, 2025)
Continuous glucose monitoring (CGM) is used more frequently among patients with chronic kidney disease (CKD), including those undergoing haemodialysis and peritoneal dialysis. However, there is a lack of information and evidence regarding CGM use in kidney transplantation (KT). Dysglycaemia is commonly observed in the transplant setting; often complicated by impaired kidney function with fluctuating glomerular filtration rates and competing influences of diabetogenic immunosuppressants, perioperative surgical stress and transplant-related complications. This narrative review, the first of its kind, examines the utility, accuracy, efficacy and clinical outcomes of CGM in KT patients. It also addresses specific transplant-related issues that may necessitate future CGM usage and highlights knowledge gaps to inform future research directions.